Analgesic Effects of Electroacupuncture at St25 and Cv12 in a Rat Model of Postinflammatory Irritable Bowel Syndrome Visceral Pain. Issue 4 (August 2018) - Zhu, Xianwei; Liu, Zhibin; Qin, Yifei; Niu, Wenmin; Wang, Qiang; Li, Lu; Zhou, Jing
Background: Treatment with electroacupuncture (EA) at ST25 and CV12 has a significant analgesic effect on postinflammatory irritable bowel syndrome (PI-IBS) visceral pain. Enterochromaffin (EC) cells and serotonin (5-hydroxytryptamine (5-HT)) are important in the development of visceral hyperalgesia. Objective: To investigate the analgesic effect and underlying mechanisms of EA at ST25 and CV12 on the treatment of trinitrobenzene sulfonic acid (TNBS)-induced PI-IBS visceral hyperalgesia in rats. Methods: After EA at ST25 and CV12, changes in abdominal withdrawal reflex (AWR), electromyography (EMG) recordings, colonic EC cell numbers, and expression of tryptophan hydroxylase (TPH), 5-HT and 5-hydroxyindoleacetic acid (5-HIAA) of TNBS-induced PI-IBS visceral hyperalgesia in rats were examined. Results: The results of AWR tests and EMG recordings indicated a significant analgesic effect of EA stimulation at ST25 and CV12on PI-IBS visceral hyperalgesia (p<0.05). In addition, the increased EC cell numbers and colonic expression of TPH and 5-HT in rats with TNBS-induced PI-IBS visceral hyperalgesia were significantly reduced by EA (p<0.05). Conclusions: EA stimulation at ST25 and CV12 can attenuate visceral hyperalgesia. This analgesic effect may be mediated via reduction of both colonic EC cell number and 5-HT concentration.